Akkermansia muciniphila in neuropsychiatric disorders: friend or foe? - Lei, Wenhui; Cheng, Yiwen; Gao, Jie; Liu, Xia; Shao, Li; Kong, Qingming; Zheng, Nengneng; Ling, Zongxin; Hu, Weiming (Frontiers in Cellular and Infection Microbiology, 2023)
An accumulating body of evidence suggests that the bacterium Akkermansia muciniphila exhibits positive systemic effects on host health, mainly by improving immunological and metabolic functions, and it is therefore regarded as a promising potential probiotic. Recent clinical and preclinical studies have shown that A. muciniphila plays a vital role in a variety of neuropsychiatric disorders by influencing the host brain through the microbiota-gut-brain axis (MGBA). Numerous studies observed that A. muciniphila and its metabolic substances can effectively improve the symptoms of neuropsychiatric disorders by restoring the gut microbiota, reestablishing the integrity of the gut mucosal barrier, regulating host immunity, and modulating gut and neuroinflammation. However, A. muciniphila was also reported to participate in the development of neuropsychiatric disorders by aggravating inflammation and influencing mucus production. Therefore, the exact mechanism of action of A. muciniphila remains much controversial. This review summarizes the proposed roles and mechanisms of A. muciniphila in various neurological and psychiatric disorders such as depression, anxiety, Parkinson’s disease, Alzheimer’s disease, multiple sclerosis, strokes, and autism spectrum disorders, and provides insights into the potential therapeutic application of A. muciniphila for the treatment of these conditions.